Endogenously heterogeneous inflation expectations and monetary policy. Issue 4 (2nd October 2021) - Saratchand, C.; Datta, Soumya
Abstract: This study adopts insights from Heterogeneous Agent Models (HAM) in order to formalize Post Keynesian insights and further develop heterodox macroeconomics. We formulate a macrodynamic model consisting of a standard Post Keynesian investment function and conflict inflation, resulting from workers and capitalists making conflicting claims over their shares in output. The central bank targets the inflation rate by employing the nominal rate of interest as an instrument. However, in a departure from standard Post Keynesian literature, expectations about inflation are endogenously heterogeneous. An endogenously determined fraction of the agents expects the inflation target of the central bank to prevail, while the rest of the agents are trend-followers. The proportion of trend followers depends directly on the proportionate deviation of the actual rate of inflation from the target rate. We examine the stability of the model and discuss some of its dynamic properties. We find that even along the steady-state neither class is able to achieve its desired share. Further, due to the endogenously heterogeneous nature of inflation expectations, any large shock to the system might destabilize it. We reexamine the effectiveness of a monetary policy that relies solely on inflation targeting in this context.